Efisisiensi Biaya Listrik Dengan Penerapan Lean Six Sigma (Studi Kasus di PT X di Cikarang) - Rahardjo, Sugeng Budi; Andriani, Andriani (DPPM UNIVERSITAS PELITA BANGSA, 2020)
PT X is a manufacturing company located in the Ejip industrial area, each month using an average of 950 KWH of electricity every month, where the electricity tariff in the area is 10% more expensive per KWH than using PLN. The ratio of electricity costs to turnover averaged 4 - 5% each month, this was very burdensome, so a project was created with the hope of a decrease of Rp. 200 million every month. The method used is Lean Six Sigma, where the project is carried out for 3 months. From the results of implementing Six Sigma, the company can find out the dominant cause and from the project costs can be reduced by 9% or 83 KWH every month.